METODE MAJELIS ULAMA INDONESIA (MUI) DALAM PENGAWASAN DAN PEMBINAAN ALIRAN KEAGAMAAN DI KABUPATEN SELUMA - Aidi Muksin (Manthiq, 2016)
Abstract: The background of this research on the method of the Indonesian Ulema Council (MUI) in the guidance and  supervision of religious  sect  in Seluma.  This study  uses  qualitative  research methods to understand the phenomenon of what  is experienced by research subjects. Data collection techniques used  were  interviews, observation and  documentation. The usefulness of this study to determine the  strategy  of the  clergy Indonesia (MUI) in coaching religious sect in Seluma. These results indicate that the method of the Indonesian Ulema Council Seluma in supervising and coaching the development of religious beliefs, which heretical, after the authors analyzed data that had writers in the field can get the authors conclude that the Indonesian Ulema Council Seluma  have a good strategy  in anticipation of the growing cult. Indonesian Ulema  Council Seluma  have  a clear  program and running  properly,  exercise direct  supervision of the study groups  that exist in Seluma  conduct control  directly or indirectly the process of learning and books  are taught in school,  the board  is very controlling institutions  da’wah Seluma,  socialize orally about  the criteria the religious to the community, socialize criteria heretical sects through books  and bulletins,  conduct a seminar on Islamic teachings, controlling  directly pratek  shamanic society, have data on the cult and spreading, making the community as a partner and in the line of duty, when the Indonesian Ulema  Council  Seluma  received reports  from the  public  both  groups  and  individuals  about  the  existence of a cult environment of citizens  of the  Indonesian Ulema  Council Seluma  immediately held  observation to further investigate if it is true then the Majelis Ulama Indonesia Seluma advises leadership and encourage the flow back to the beaten path, if they do not want it to be handed over to the law enforcement authorities. The authors conclude that the board  of the Indonesian Ulema Council Seluma  own srtategi well in anticipation of the development of heretical sects but not maximized. In the implementation of the Indonesian Ulema Council committee Seluma also carry out their duties by the Qur’an and the Sunnah  of the Prophet the board of the Indonesian Ulema Council has full responsibility to anticipate the growth of religious denominations and passed a fatwa to Muslims.